The effects of Vitamin C on sperm quality parameters in laboratory rats following long-term exposure to cyclophosphamide - Sheida Shabanian; Farnoosh Farahbod; Mahmoud Rafieian; Forouzan Ganji; Afshin Adib (Wolters Kluwer Medknow Publications, 2017)
Cyclophosphamide is a widely used medication and can cause oxidative stress. This study was conducted to investigate the effects of Vitamin C on reproductive organs' weight and the quality of sperm parameters in laboratory rats. In this experimental study, 40 rats were randomly assigned into five groups of eight each. Distilled water (DW) group received only food and water, Group 2 was administered with drug solvent (DW) by gavage, Group 3 intraperitoneally administered with 1.6 mg/kg cyclophosphamide, Group 4 gavaged Vitamin C at 0.88 mg/kg, and Group 5 administered with effective doses of Vitamin C and cyclophosphamide by gavage with 1-h intervals. Sperm parameters of the samples were taken from distal epididymis and tissues were studied, and the data were analyzed by SPSS version 22. The lowest weight of testicles and epididymis was seen in cyclophosphamide-exposed rats and the highest weight of testicles and epididymis in Vitamin C-exposed rats (P < 0.05). The highest motility, progression, viability, and count of sperm were seen in the Vitamin C-treated group and the lowest in the cyclophosphamide-exposed group. The highest proportion of sperm anomalies was seen in the cyclophosphamide-exposed group. Vitamin C, as an antioxidant, can be effective on some of the sperm parameters and can reduce cyclophosphamide-induced complications in animal model.